2017
DOI: 10.1016/j.yexcr.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

High-content image informatics of the structural nuclear protein NuMA parses trajectories for stem/progenitor cell lineages and oncogenic transformation

Abstract: Stem and progenitor cells that exhibit significant regenerative potential and critical roles in cancer initiation and progression remain difficult to characterize. Cell fates are determined by reciprocal signaling between the cell microenvironment and the nucleus; hence parameters derived from nuclear remodeling are ideal candidates for stem/progenitor cell characterization. Here we applied high-content, single cell analysis of nuclear shape and organization to examine stem and progenitor cells destined to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…We found that cell area increased progressively with age while nuclei size and shape became smaller and less elongated. Alterations in nuclear biology during MSC aging continue to be dissected as a way to characterize cell state [62, 63]. In keeping with the trends mentioned above, we found strong correlations between age and adipogenic potential, consistent with both our previous findings as well as that of the field.…”
Section: Discussionsupporting
confidence: 91%
“…We found that cell area increased progressively with age while nuclei size and shape became smaller and less elongated. Alterations in nuclear biology during MSC aging continue to be dissected as a way to characterize cell state [62, 63]. In keeping with the trends mentioned above, we found strong correlations between age and adipogenic potential, consistent with both our previous findings as well as that of the field.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous gene expression analysis shows several clusters of genes upregulated early during lineage divergence, including cell cycle genes and nuclear splicing factor genes, especially Nuclear mitotic apparatus protein, NuMA 46 . Morphotextural descriptors of NuMa were able to distinguish phenotypes with greater efficacy when combined with descriptors for actin filaments in MSCs 47 .…”
Section: Discussionmentioning
confidence: 99%
“…1 , 2 , and 5 ) and regulatory functions in the nucleus. Uncovering NuMA’s nuclear functions may in turn help understand why its localization varies depending on cell phenotype ( Knowles et al, 2006 ; Vega et al, 2017 ). Similarly, it will shed light on why NuMA’s expression level and impact on nuclear architecture vary dramatically between epithelial cells and highly specialized or terminally differentiated cells ( Merdes and Cleveland, 1998 ).…”
Section: Discussionmentioning
confidence: 99%